Abrasive water jet experimentation on zirconium boride and boron carbide reinforced molybdenum metal matrix. (2020) - Arravind, R.; Sankar, V.; Marichamy, S.; Stalin, B.
Abstract: In metal industries, molybdenum has placed an important role because of its properties and applications. It has high strength, hardness, electrical conductivity, resistance to wear and corrosion. This paper deals with parametric effects of abrasive water jet machining of Molybdenum Metal Matrix (Mo-MMC) which is made from stir casting technique. The two reinforcements such as Boron Carbide (B4 C) and Zirconium Carbide (ZrC) are considered with a mixture of compositions such as 2, 4 and 6% weight proportions. Further development of work and performance of metal properties, the prepared samples are involved for testing of materials. Based on these compositions, 6% of an alloy is provided the best performance. Hence, it has forwarded to the further investigations like as Abrasive Water Jet Machining (AWJM) process. The machinability characteristics are studied through this mechanical energy based method. The response of Material Deletion Rate (MDR) is measured through the change of input constraints such as water pressure, abrasive flow rate and traverse speed. The optimal parameters are derived from Taguchi method. The parametric effects on material deletion rate are investigated with the help of Pareto charts and Analysis of variance (ANOVA).